Community’s Disaster Preparedness and Response in the Context of Typhoons - Gapuz, Christopher (Future Science / FSH-PH Publications, 2026)
This study aimed to determine the community’s disaster preparedness and response in the context of typhoons. A descriptive research design combining quantitative and qualitative approaches was employed. A self-constructed survey questionnaire and in-depth interviews served as the main instruments for data collection. Simple random sampling was used to select 152 respondents for the survey, while interviews involved five residents from high-risk areas and four experts, including the CDRRMO Division Chief, BFP Fire Marshall, and two barangay officials. Most respondents were aged 21–30, predominantly female, and had lived in Sitio Ibaba, Barangay Pallocan West, Batangas City, for ten years or more. Findings revealed that residents practiced pre-disaster preparations, such as charging flashlights and mobile phones and stocking essential food and medicine. In rescue and relief operations, respondents coordinated with authorities and assisted neighbors before, during, and after typhoon events. Communication was primarily through television, radio, and megaphones used by barangay officials. Residents assessed the City Disaster Risk Reduction and Management Council (CDRRMC) services positively in terms of program implementation and response and readiness, with the only limitation being the availability of printed materials. Overall, the council provided effective support through training programs, seminars, sufficient rescue and evacuation equipment, and accessible emergency hotlines. To further enhance preparedness and response, the study proposes the development and distribution of printed materials tailored to the community. These findings highlight practical strategies for improving community resilience and emergency coordination during typhoons, offering evidence-based recommendations for local governments, disaster management agencies, and community leaders.